Motor imagery and cortico-spinal excitability: A review. Issue 3 (2nd April 2016) - Grosprêtre, Sidney; Ruffino, Célia; Lebon, Florent
Abstract: Motor imagery (MI) has received a lot of interest during the last decades as its chronic or acute use has demonstrated several effects on improving sport performances or skills. The development of neuroimagery techniques also helped further our understanding of the neural correlates underlying MI. While some authors showed that MI, motor execution and action observation activated similar motor cortical regions, transcranial magnetic stimulation (TMS) studies brought great insights on the role of the primary motor cortex and on the activation of the cortico-spinal pathway during MI. After defining MI and describing the TMS technique, a short report of MI activities only at cortical level is provided. Then, a main focus on the specificities of cortico-spinal modulations during MI, investigated by TMS, is provided. Finally, a brief overview of sub-cortical mechanisms gives importance to the activation of peripheral neural structures during MI.